Role of non-governmental organizations in moving toward universal health coverage: A case study in Iran - Sanadgol, Arman; Doshmangir, Leila; Khodayari-Zarnaq, Rahim; Sergeevich Gordeev, Vladimir (Frontiers in Public Health, 2022)
Background: Delivering essential health services through non-governmental organisations (NGOs) could facilitate moving towards universal health coverage (UHC), especially in low- and middle-income countries. This study investigates the viewpoints of Iranian health system experts and executive stakeholders on the role of NGOs in moving towards UHC. Method: We conducted 33 semi-structured interviews with health policymakers, NGO representatives at the national and provincial level, and other key informants and analysed using content analyses methods, using MAXQDA 12. The inductive-deductive approach was used for qualitative data analyses. Result: Based on the thematic analysis of interviews and document reviews, nine main themes and one hundred and five sub-themes were identified. Each theme was categorised based on NGO-, society-, and government-related factors. Conclusion: Recognising the critical role of NGOs and their contribution in moving towards UHC is essential, particularly in the local context. Collaboration between NGO stakeholders and the government could facilitate moving towards UHC.